Variant of alternating phase focusing with the stepped change of the synchronous phase - Bomko, V.A.; Kobets, A.P.; Ptukhina, Z.E.; Tishkin, S.S. (Вопросы атомной науки и техники, 2004)
In the paper the calculation of the accelerating structure with the stepped change of the synchronous phase is presented. The method is tested for the calculation of the accelerating structure and He⁺ beam with A/q=4 in the energy range from 30 keV/n to 0.975 MeV/n.